Scaling effects on hypoxia tolerance in the Amazon fish Astronotus ocellatus (Perciformes: Cichlidae): Contribution of tissue enzyme levels - Val, Vera Maria Fonseca Almeida e; Val, Adalberto Luis; Duncan, Wallice Luiz Paxiuba; Souza, Fabiana C A; Paula-Silva, Maria Nazaré N.; Land, Stephen C. (Comparative Biochemistry and Physiology - B Biochemistry and Molecular Biology, 2000)
Astronotus ocellatus is one of the most hypoxia tolerant fish of the Amazon; adult animals can tolerate up to 6 h of anoxia at 28°C. Changes in energy metabolism during growth have been reported in many fish species and may reflect the way organisms deal with environmental constraints. We have analyzed enzyme levels (lactate dehydrogenase, LDH: EC 1.1.1.27; and malate dehydrogenase, MDH: EC 1.1.1.37) in four different tissues (white muscle, heart, liver, and brain) from different-sized animals. Both enzymes correlate with body size, increasing the anaerobic potential positively with growth. To our knowledge, this is the first description of scaling effects on hypoxia tolerance and it is interesting to explore the fact that hypoxia survivorship increases due to combining effects of suppressing metabolic rates and increasing anaerobic power as fish grow. Copyright (C) 2000 Elsevier Science Inc.
Keywords: Lactate Dehydrogenase; Malate Dehydrogenase; Aerobic Metabolism; Animals Tissue; Controlled Study; Energy Metabolism; Enzyme Activity; Enzyme Localization; Fish; Glycolysis; Growth; Hypoxia; Metabolic Rate; Nonhuman; Priority Journal; Animalsia; Astronotus; Astronotus Ocellatus; Astronotus Ocellatus; Cichlidae; Perciformes